(3cJGH GdOQI GdHjVGA hGdjGbhJI GdMeQGA GdeQJHI Ydi GddhGFM GdbOSjI hGdahGFO GdMcejIs - (3Ydj LdHj GdQhejs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdYGde ef OQI HjVG hLYd GddhM GdeMahX ef jGbhJg MeQG EYde Cf GdCHNQI GdeMJHSI ai GdCQV YfO ESJjdGA HQhOI GdTJGA YdjgG s
(3BNQgG (B:s
(3EYde Cf GdeGA GdNGdO EPG TeY Hg GdUHZ hHGdeGA GdPgHi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs